Ativa idade no lar - Souto, Deisiane Oliveira; do nascimento, Letícia Santos Ferreira; Santos, Natália Sthephanie; da Silva, Marlene Bento; Barral de Lacerda, Tatiana Teixeira (Sinapse Múltipla, 2015)
Trabalho apresentado na Mostra de Pesquisa e extensão (Mostra PEX) na UC Minas em Betim em abril de 2015